2010
DOI: 10.1142/s0129167x10006574
|View full text |Cite
|
Sign up to set email alerts
|

Puiseux Power Series Solutions for Systems of Equations

Abstract: We give an algorithm to compute term by term multivariate Puiseux series expansions of series arising as local parametrizations of zeroes of systems of algebraic equations at singular points. The algorithm is an extension of Newton's method for plane algebraic curves replacing the Newton polygon by the tropical variety of the ideal generated by the system. As a corollary we deduce a property of tropical varieties of quasi-ordinary singularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Later it was established (in full generality) in [SS04]. Extensions to arbitrary codimension ideals and arbitrary valuations have been done subsequently (see for example [AILdM10,JMM08,Aro10]).…”
Section: -Introductionmentioning
confidence: 99%
“…Later it was established (in full generality) in [SS04]. Extensions to arbitrary codimension ideals and arbitrary valuations have been done subsequently (see for example [AILdM10,JMM08,Aro10]).…”
Section: -Introductionmentioning
confidence: 99%
“…The second part of this paper gives an explanation of Newton-Puiseux expansions with a view to applying them to dimensionless equations derived via the method of the previous sections. The development follows [1], which presents explicit formulae for such expansions, extending the classical theory [2,5,14]. A Newton-Puiseux expansion is a fractional power-series solution of an algebraic equation or a system of such equations [14,15].…”
Section: Dimensional Analysis In the Differential Equation Casementioning
confidence: 99%
“…The purpose of this paper is to demonstrate that recent new results [1] in the theory of fractional power series solutions of algebraic equations may be placed in a more general setting, and that this makes possible further developments in the theory of such equations [2] . In particular, it is shown that ideas from algebraic geometry, especially the theory of toric varieties and ideals [3], provide a basis for new computational tools which draw on, and extend, currently available tools within the flourishing research area of computational algebraic geometry [4].…”
Section: Introductionmentioning
confidence: 98%
“…In [5], we extend Mc Donald's algorithm to algebraic varieties of arbitrary codimension. To do this, we do not work with polygons but with dual fans and, instead of working with equations restricted to edges, we work with initial equations.…”
Section: Introductionmentioning
confidence: 99%